Estradiol protection against toxic effects of catecholamine on electrical properties in human-induced pluripotent stem cell derived cardiomyocytes. (1st March 2018) - El-Battrawy, Ibrahim; Zhao, Zhihan; Lan, Huan; Schünemann, Jan-Dierk; Sattler, Katherine; Buljubasic, Fanis; Patocskai, Bence; Li, Xin; Yücel, Gökhan; Lang, Siegfried; Nowak, Daniel; Cyganek, Lukas; et al.
Abstract: Background and purpose: Previous studies revealed that Takotsubo cardiomyopathy (TTC), a transient disorder of ventricular dysfunction affecting predominantly postmenopausal women, is associated with acquired long QT syndrome and arrhythmias, but the exact pathophysiologic mechanism is unknown. Our aim is to investigate the electrophysiological mechanism for QT-prolongation in TTC-patients by using human induced pluripotent stem cell-derived cardiomyocytes (hiPSC-CMs). Methods: hiPSC-CMs, which were generated from human skin fibroblasts of three healthy donors, were treated by estradiol (10 μM for one week) and a toxic concentration of isoprenaline (Iso, 1 mM for 2 h). Patch clamp techniques, qPCR and fluorescence-activated cell sorting (FACS)were employed for the study. Key results: Iso enhanced late INa and suppressed Ito and thus prolonged the action potential duration (APD), suggesting possible reasons for arrhythmias in TTC. Iso elevated the production of reactive oxygen species (ROS). N -acetylcystein (1 mM), a ROS-blocker, abolished the effects of Iso on late INa and Ito . H2 O2 (100 μM) mimicked Iso effects on late INa and Ito . These data indicate that the effects of Iso were mediated by ROS. Metoprolol (1 mM), a beta-blocker, prevented the effects of Iso on late INa and APD, confirming the adrenoceptor-dependent effects of Iso. Estradiol treatment prevented the APD-prolongation, attenuated the enhancement of INa, diminished the reduction of Ito, suppressed ROS-production induced by Iso and reduced the expression levels of adrenoceptors, suggesting protective effects of estragon against toxic effects of catecholamine. Conclusions: Estradiol has protective effects against catecholamine excess and hence reduction in estrogen level may increase the risk of acquired long QT syndrome in TTC.